The location of emotional intelligence measured by EQ-i in the personality and cognitive space: Are there gender differences? - Tommasi, Marco; Sergi, Maria Rita; Picconi, Laura; Saggino, Aristide (Frontiers in Psychology, 2023)
Introduction Emotional Intelligence (EI) is first described by Salovey and Mayer as the ability to perceive and understand emotions and the ability to use them as supports for thoughts. Despite the great notoriety of EI, its definition remains not completely clear. An operative definition of EI can be achieved by studying its connection with other individual characteristics as gender, personality traits and fluid intelligence. Method The sample was composed by 1063 Italian subjects. 330 participants were employed (31.0%; 57.9% males; 702 were university students (66.0%; 38.7% males). The Emotional Quotient Inventory (EQ-i), one of the most used questionnaires in literature, was used to measure EI. The exploratory structural equation modelling (ESEM) was used to assess the role of personality traits (five-factor model of personality) and fluid intelligence in the EI. Statistical analyses on differences between males and females means of total and subscale EQ-i scores were estimated to evaluate if EI, measured by EQ-i, is influenced by gender, .Furthermore, a Multigroup Confirmatory Factor Analysis was conducted to assess measurement invariance in relation to gender groups. Results EI, measured by EQ-i, is prevalently connected with personality traits rather than fluid intelligence. Furthermore, males outperformed females in the Intrapersonal and Stress Management EI factors and female outperformed males in the Interpersonal EI factor. No difference The means of the EI total score and EI latent general factor did not differ between gender groups.